Complex Systems in Knowledge-based Environments: Theory, Models and Applications - Tolk, Andreas; Jain, Lakhmi C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
This volume comprises a selection of state-of-the-art contributions to topics dealing with Complex Systems in the Knowledge-based Environment. Complex systems are ubiquitous. Examples comprise, but are not limited to System of Systems, Service-oriented Approaches, Agent-based Systems, and Complex Distributed Virtual Systems. All these are application domains that require knowledge, engineering, and management methods beyond the scope of traditional systems. The chapters in this book deal with a selection of relevant topics, ranging from uncertainty representation and management to the use of ontological means in support of large-scale business integration. All contributions were invited based on the special recognition of the contributing authors in their field during workshops and symposia. By bringing all these different aspects together in one volume, our intent was first to present a variety of tools to the reader in support of his studies and work, and second to show how the different facets presented in the chapters are complementary contributing towards an emerging discipline to cope with complex systems. The common denominator of all chapters is the use of knowledge-based methods, in particular ontological means. The chapters are categorized into theory contributions and practical applications. We hope that this volume will help researchers, students, and practitioners in coping with the challenges of integration, operation, and evaluation of complex systems.
An Introduction to Complex Systems in the Knowledge-Based Environment -- Uncertainty Representation and Reasoning in Complex Systems -- A Layered Approach to Composition and Interoperation in Complex Systems -- Ontology Driven Data Integration in Heterogeneous Networks -- Complexity and Emergence in Engineering Systems -- Feature Modeling: Managing Variability in Complex Systems -- Semantic Robotics: Cooperative Labyrinth Discovery Robots for Intelligent Environments -- Principles for Effectively Representing Heterogeneous Populations in Multi-agent Simulations -- Ontology Meets Business - Applying Ontology to the Development of Business Information Systems.
Keywords: Engineering; Artificial intelligence; Applied mathematics; Engineering mathematics; Engineering; Appl.Mathematics/Computational Methods of Engineering; Artificial Intelligence (incl. Robotics).; Electronic books